Effects of teaching strategies supported by information and communication technologies on satisfaction and learning of college students - Torres, Andreia Araújo Lima (2015)
Studies show that Brazil is currently experiencing a double burden of nutritional problems related to malnutrition and other nutritional deficiencies on one side and the onset of the binomial overweight / obesity on a population scale on the other side. Such disorders are linked to complex factors. Therefore it is understood that their resolution will only be possible with the involvement of the whole society. In Brazil, health courses do not address, except for nutritionists and, to some extent, nurses, specific contents on human nutrition, compromising the action of other health professionals in the area. This study aims to contribute to the teaching of basic nutrition content in a course offered to undergraduate healthcare students of a public college in Brazil. The course was restructured in order to meet the educational objectives previously set. New features, educational technologies and materials based on instructional theories and instructional design were developed and included on the course. The main results on satisfaction and learning are presented.